Tracking for inspection in energy transmission power lines using unmanned aerial vehicles: a systematic review of current and specific literature - Martins, Wander M.; Dantas Filho, Antonio J.; de Jesus, Leandro D.; de Souza, Adler D.; Ramos, Alexandre C. B.; Pimenta, Tales C. (IAES International Journal of Robotics and Automation (IJRA), 2020)
Power transmission lines are of great importance for the operation of all sectors of society, such as commerce, industry and public agencies. To ensure reliability and availability of power supply, regular and occasional inspections are conducted, mostly using patrol with binoculars, helicopters or truck cranes. Research is being developed using unmanned aerial vehicle (UAV) to make this activity autonomous, faster, safer, and less costly. The present work aims to analyze research related to the autonomous control of the UAV along the transmission lines through a systematic review of the literature (SRL), apply a viable solution and to verify the possible lacuna in this state of the art. Improvements in safety, computational process and energy efficiency with low-cost were identified. The results presented can help the research community to perform the working this state of art, from the suggestions of autonomous tracking of transmission lines.